Distributional patterns of herbivore megamammals during the Late Pleistocene of South America - GALLO,VALERIA (2013)
The geographic distribution of 27 species of the South American megafauna of herbivore mammals during the Late Pleistocene was analyzed in order to identify their distributional patterns. The distribution of the species was studied using the panbiogeographical method of track analysis. Six generalized tracks (GTs) and two biogeographic nodes were obtained. The GTs did not completely superpose with the areas of open savanna present in Pleistocene, nor with the biotic tracks of some arthropods typical of arid climate, indicating that these animals avoided arid environment. Overall, the GTs coincided with some biogeographic provinces defined on the basis of living taxa, indicating that certain current distributional patterns already existed in Pleistocene. The biogeographic nodes coincided with the borders between the main vegetal formations of the Pleistocene, showing that the type of vegetation had great influence in the distribution of the mammalian megafauna. The node 1 confirmed the existence of contact zones between paleobiogeographic regions near Argentina-Uruguay border. The node 2 connects the Brazilian Intertropical regions.